First detection of human dirofilariasis in South Africa - Krishnee Moodley; Chetna N. Govind; Abdool K.C. Peer; Marissa van der Westhuizen; Dharmesh Parbhoo; Lisa Ming Sun; Desiree C. du Plessis; John A. Frean (MDPI AG, 2015)
Humans are occasionally inadvertently infected with dirofilariae, the zoonotic nematodes. We report two cases of human dirofilariasis in South Africa, an area apparently non-endemic for this infection. Dirofilariasis is frequently misdiagnosed, so increased awareness of this entity in areas that are non-endemic is essential for prevention of inappropriate investigations and invasive therapy.